How College Students Understand Their Self-Control Development: A Qualitative Analysis. Issue 3 (3rd July 2017) - Cliburn Allen, Cara; Glanzer, Perry
Abstract: Recent research has shown the importance of the positive benefits of high-levels of self-control for both individuals and society. Yet, we know only a limited amount about how college students understand and apply self-control. This qualitative study examined how a national sample of 75 students defined self-control, whether or not they believed that they had developed self-control in college, and where they found help developing it. The analysis illuminated situational strategies that students found helpful in strengthening the self-control muscle, such as advice from faculty and scheduling. The findings also affirm the important role that trusted relationships play in self-control development and guidance.